The evolution of innovation strategy: Studied in the context of medical device activities at the pharmaceutical company Novo Nordisk A/S in the period 1980-2008 - Arne Stjernholm Madsen (Copenhagen Business School (CBS), 2012)
Increased globalization in business competition makes the ability to innovate and to redefine strategy crucial to a company. An interesting question however is if a management team can control innovation and strategic renewal of the company at all; or do such changes emerge, driven by external events or by bottom-up processes in the organization? The present research project addresses some of these issues through the overall research question “How does innovation strategy evolve?” The research question is examined in a specific empirical context. Since 2001, I have worked as an internal innovation consultant at Novo Nordisk A/S; a pharmaceutical firm founded in 1923 operating in a well established industry (insulin for diabetes treatment), characterized by intensive investments in Research and Development. I took advantage of this unique access to the internal life of an organization and consequently set up my research project as a longitudinal in-depth case study of the medical device innovation activities at Novo Nordisk A/S covering the period 1980-2008. The study specifically analyzes the relationship between the classic core product of the firm (insulin) and complementary products (medical devices, such as insulin `pens'), which hold the potential to either enhance the value of the core product, or to become a distinct business of its own. Burgelman's evolutionary theory of strategy making, especially his `internal ecology model' (Burgelman 1991, 2002), has been chosen as the basic theoretical framework for the project. Some expansions of this framework, however, were needed. First, the present study puts greater emphasis on analyzing the external environment and its influence on internal strategy processes. Second, the analysis includes the role of management cognition, especially the notion of the corporate dominant logic (Prahalad & Bettis, 1986; Bettis & Prahalad, 1995), understood as an enduring top management worldview or mindset based on reinforcement of experiences from the past. With regard to results, the present study identifies a more entrepreneurial role of the top management driven induced strategy process than traditionally described in evolutionary theory. In this case study, strategic variation and trial-and-error learning is not restricted to the autonomous initiatives in the `internal ecology'; on the contrary, top management cognition creates strategic visions or hypotheses, which are enacted as experiments in the market, for example in the form of new product categories. External feedback determines the destiny of these strategic experiments. Thereby innovation strategy (in case, for medical devices) serves as a strategic laboratory at corporate level, so to speak. The device-based strategic experiments face the challenge of escaping the gravity of the dominant logic, which repeatedly pulls the strategy back towards the well-known success formula, centered on the drug itself (i.e. the insulin). Thus, the induced strategy process mediates core assets (pharmaceutical drugs) and complementary assets (medical devices), by swinging the pendulum between cycles of innovation strategy which define the devices as core or complementary respectively. Hence, the balance between what is defined as core and what is defined as complementary in the corporate innovation strategy seems to be dynamic and negotiable. As a consequence of the cycles of strategic experimentation, the corporate induced strategy process acts as a force of strategic entrepreneurship, seen over extended time. The implications for research point towards a new paradigm of strategic research in the `middle ground' between rational choice theory and evolutionary theory, as proposed by Gavetti & Levinthal (2004). The present research project suggests that a firm's ability for strategic adaptation depends both on strategic context determination of autonomous initiatives in the `internal ecology' and on ability to enact induced strategic experiments with alternating innovation strategies in the market. This theory of `inbound' and `outbound' strategic search establishes a dynamic understanding of the corporate induced strategy process. In this understanding, innovation strategies act as hypotheses, which create strategic dissonance between vision and reality and thereby drive strategic learning. The implications for management practice are first recognition of how fortunate it has been for Novo Nordisk to sustain the core business strategy, protected by the dominant logic. This fact relates to a background where the core market proved to hold immense growth potential, and the industry was relatively stable compared to for instance the IT industry. On the other hand, Novo Nordisk's success is partly due to cycles of strategic experiments with complementary assets for innovation, in case medical devices. Top management initiated these explorative experiments and the learning was utilized for expansion of the position within the core business. Hence, one can conclude that a company should explore and utilize the value of complementary assets, since these are perfect tools for strategic experimentation without risking the core business.
hdl:10398/8453
Keywords: 650